Fóruns no ambiente Teleduc: reflexões sobre o papel dos mediadores e estratégias de gerenciamento de debates - Funo, Ludmila Belotti Andreu [UNESP] (2015)
Online discussion forums have been widely used in internet-mediated courses and blended courses. In these learning contexts, the mediator's (or tutor's) role in supporting successful learning is of considerable importance. Firstly, the present article discusses some studies in which the mediator's role in online learning environments is emphasized. Secondly, we use this discussion to support our qualitative case-study analysis, in which we investigated mediators' debate-management strategies in TelEduc virtual forums. Lastly, we propose a reflective framework about management strategies in forums in virtual learning platforms.